Handbook of infrared optical materials - Klocek, Paul (Optical engineering (Marcel Dekker, Inc.), 1991)
This thorough handbook provides a substantial background in infrared optics and offers quick access -- via alphabetical listing -- to a wealth of practical information on numerious materials applied in the field, containing physical property data on over 100 traditional, new, and emerging crystalline and glass infrared optical materials in over 500 data sheets, tables, and figures.